Self-reliance and Social Networks: Explaining Refugees' Reluctance to Relocate from Kakuma to Kalobeyei. (13th April 2020) - Betts, Alexander; Omata, Naohiko; Sterck, Olivier
Abstract: In 2016, refugees in the Kakuma camps in Kenya were offered the opportunity to relocate to the new Kalobeyei settlement, which ostensibly offered a better set of opportunities. While it was portrayed by the international community as objectively better for refugees' autonomy and socio-economic prospects, most refugees in Kakuma viewed the opportunity differently. Less than 16 per cent of refugees who heard about Kalobeyei were willing to be resettled there if land were provided. For refugees, the main justifications for the reluctance to move were linked to the likely disruption to existing social networks. This example of 'relocation for self-reliance' has wider implications for how we conceptualize self-reliance. Although the United Nations High Commissioner for Refugees (UNHCR)'s definition of refugee self-reliance recognizes that it applies to the community level as well as the individual level, self-reliance programmes that exclusively target individuals risk rejection by communities unless they also take into account the importance of social networks.